Exploring the efficacy of the singing method for teaching nglegena javanese letters to fourth-grade students in an elementary school - Maghfiroh Apristya Laily; Sularso Sularso; Mwansa Edward Chabu (International Journal of Education and Learning, 2024)
Students' difficulties in learning Javanese script are caused by several factors, such as challenges in distinguishing one character from another, low interest and motivation to learn, and limited access to educational materials and resources. This study aims to evaluate the effectiveness of the singing method as a learning strategy in teaching Javanese Nglegena script. This study uses a participatory qualitative approach with data collection techniques through interviews and observations of research subjects, namely fourth-grade students at an elementary school in Yogyakarta. The research sample consisted of 28 students, consisting of 16 boys and 12 girls. The results of the study showed that the singing method provided a more positive and interesting learning experience. Quantitatively, there was an increase in students' interest and motivation in learning, which contributed to a more interactive and enjoyable learning process. The main contribution of this study is the development of a more effective Javanese Nglegena script learning model through the singing method. This model can be adopted by Javanese language educators to increase students' interest in learning Javanese script. In addition, this method has also been proven to help students memorize material faster and maintain memory longer.